Nature forces and friction laws to wear resistance steel abrasive - Дворук, В.І.; Борак, К.В.; Добранський, С.С. (Problems of Tribology, 2016)
The results of experimental studies using direct phenomenological methods have shown that friction and wear resis-tance when sliding on steel monolith defined by its resistance to lateral spread cracks on the verge of plastically deformed zone of the damaged surface layer of deformed metal. Said resistance is controlled by the degree of localization of deforma-tion in the surface layer and its mechanical condition.